Diretrizes para a educação ambiental e o plano plurianual de gestão da Etec de Ibaté (SP) - Silva, Shirlei Gomes da (2023)
The National Common Curricular Base (BNCC), the National Environmental Education Policy (PNEA), and the 2030 Agenda are documents that have pointed towards contemporary good educational practices. In this regard, the aim of this study was to analyze to what extent the Plurianual Management Plan (PPG) of the State Technical School (ETEC) in Ibaté-SP encompasses pedagogical and technical-scientific aspects in favor of Environmental Education (EE) based on reference documents. To achieve this, the study conducts a specific survey of literature convergence, identifies favorable aspects of science, technology, and pedagogical practices in EE, and analyzes recommendations from the BNCC, PNEA, and 2030 Agenda related to the practices developed in the Political-Pedagogical Project (PPP) and PPG. Methodologically, this study begins with scientific and academic investigation, alongside a thorough analysis of the listed documents. This approach reveals convergence and the presence of positive aspects among the documents, including the use of various technical approaches. This analysis emphasizes the need to strengthen EE both in theoretical and practical realms in the daily school context, recognizing its significance in cultivating environmental awareness and shaping active citizens in environmental advocacy. By presenting this analysis, the study aims to contribute to the enhancement of education quality in the school environment and to promote sustainable practices beyond the school community. Furthermore, it aims to validate the construction of new knowledge in Science, Technology, and Society (STS) through the identification of potential gaps and challenges in the process, stimulating reflection on a more conscious, critical, and sustainability-committed organizational culture.